The Role, Management and Economic Function of a Natianal Park with Special Reference to Kaziranga - Das, B. N. (Indian Forester, 1969)
The United States of America is the first country in the world known to have established a national park namely the Yellow Stone National Park in 1872. This was followed by formation of a number of National Parks in Africa and Europe. In India the first National Park namely the Hailey National Park was established in 1935 in the State of Uttar Pradesh. Assam government have now passed the Assam National Park Act 1968 in order to constitute Kaziranga Wild Life Sanctuary into a National Park. Kaziranga noted for its great Indian rhinoceros holds promise to be one of the best centres of tourist's attractions in India. A well-managed national park may serve many useful purposes to the people. Besides being a place of recreation and enjoyment for the visitors it offers fields for ecological study of flora and fauna of a country. Its econonomic value also is of considerable importance to a developing country. Besides the value obtained from the disposal of the surplus stock of valuable faunal resources of a national park, the economic benefit derived from the foreign tourists in the form of foreign exchange is also of great value. In an over populated country like India depending on agricultural economy the protection of the national parks presents a difficult task because of the demand for more land and other natural resources from limited forest land for expanding population. Kaziranga National Park has the same problem as it is surrounded by a large agricultural population. Proper education on the value of the national parks to the country as a whole is a pre-requisite to win their co-operation. The main danger to Kaziranga however remains from the rhino poachers. The trade on rhino horn is flourishing in the East Asian countries. The superstition of the magical healing power of rhino horn would need to be banished from the minds of the people of the east if rhino is to be saved from extinction in near future. The world body like the Survival Service Commission of the I. U. C. N. could perhaps take up some work in this line.